SWOT analysis of telecenter development as a rural community empowerment strategy - Christopher, Perumal; Novel, Lyndon; Zaini, Sakawi (IASE., 2023)
This research investigates the effects of using information and communication technology (ICT) as a method to empower the community in Pos Balar, a rural area inhabited by the Orang Asli people. The method used for this study is a SWOT analysis, which looks into the strengths, weaknesses, opportunities, and threats of setting up a telecenter in the area. To gather information, the study involved detailed interviews with ten individuals and a group discussion with local leaders. The results indicate that establishing a telecenter can offer new ways of communication, serve as a central point for information, and improve the efficiency of local authorities. This can lead to new possibilities and skill development within the community, and the telecenter could become a symbol of community progress. However, there are several challenges, such as a lack of technical skills in ICT, a gap in digital access and understanding, language barriers, inconsistency in community unity, frequent changes in administration, infrastructure issues, and misuse of technology. The study also points out opportunities, including forming partnerships, enhancing access to education and health services, improving connections to markets, and offering online government services. On the other hand, threats like limitations in road infrastructure, market challenges, concerns about privacy and security, and the impact on traditional ways of earning a living were identified. Overall, this research underlines the significance of rural ICTs, as seen through a SWOT analysis. It shows the value of using new communication technologies to build networks and partnerships across various sectors and stakeholders. The study stresses the necessity of a united, collaborative, and inclusive approach in the local community. This is crucial for ensuring sustainable and fair development in rural areas, aided by advancements in ICT.